2015
DOI: 10.1063/1.4929589
|View full text |Cite
|
Sign up to set email alerts
|

W-band EPR studies of high-spin nitrenes with large spin-orbit contribution to zero-field splitting

Abstract: First W-band 94 GHz EPR spectra of randomly oriented triplet, quintet, and septet nitrenes formed during the photolysis of 1,3,5-triazido-2,4,6-tribromobenzene in cryogenic matrices are reported. In comparison with conventional X-band 9 GHz electron paramagnetic resonance (EPR) spectroscopy, W-band EPR spectroscopy allows the detection and complete spectroscopic characterization of all paramagnetic species formed at different stages of the photolysis of aromatic polyazides. This type of spectroscopy is of para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 39 publications
5
25
0
Order By: Relevance
“… The contribution of the spin‐orbit (SO) coupling to parameter D is one order of magnitude greater than the contribution of the spin–spin (SS) interaction. The main SO contribution is the SOMO→SOMO spin‐flip interaction between excited singlet and ground triplet states (Table S3). The PBE/Ahlrichs‐DZ level of theory is universal and describes the experimental results for all known triplet phosphinidenes (Table ), as well as for high‐spin nitrenes The calculated components ( A x and A y ) of hyperfine structure tensor A are similar to those obtained from the experimental spectrum, see Table . …”
Section: Methodssupporting
confidence: 56%
“… The contribution of the spin‐orbit (SO) coupling to parameter D is one order of magnitude greater than the contribution of the spin–spin (SS) interaction. The main SO contribution is the SOMO→SOMO spin‐flip interaction between excited singlet and ground triplet states (Table S3). The PBE/Ahlrichs‐DZ level of theory is universal and describes the experimental results for all known triplet phosphinidenes (Table ), as well as for high‐spin nitrenes The calculated components ( A x and A y ) of hyperfine structure tensor A are similar to those obtained from the experimental spectrum, see Table . …”
Section: Methodssupporting
confidence: 56%
“… The contribution of the spin‐orbit (SO) coupling to parameter D is one order of magnitude greater than the contribution of the spin–spin (SS) interaction. The main SO contribution is the SOMO→SOMO spin‐flip interaction between excited singlet and ground triplet states (Table S3). The PBE/Ahlrichs‐DZ level of theory is universal and describes the experimental results for all known triplet phosphinidenes (Table ), as well as for high‐spin nitrenes The calculated components ( A x and A y ) of hyperfine structure tensor A are similar to those obtained from the experimental spectrum, see Table . …”
Section: Methodssupporting
confidence: 56%
“…Our interest in the EPR spectra of organic phosphinidenes was motivated by the study of the heavy‐atom effect on magnetic anisotropy as a continuation of our previous studies . Our initial EPR measurements in photolyzed frozen solutions with precursors 1 a and 1 b showed that the spectrum of photolytic product 2 (Scheme ) is significantly different from that reported in Ref.…”
Section: Methodsmentioning
confidence: 88%
See 1 more Smart Citation
“…However, the best conditions for stabilization and further electron paramagnetic resonance (EPR) studies of all types of septet trinitrenes are achieved on works in solid inert gases at 4–16 K . Using this matrix‐isolation technique, it has been shown that the photolysis of 1,3,5‐triazidobenzenes results in the formation of septet trinitrenes in more than 95% yield . On contrast, the photolysis of 2,4,6‐triazido‐1,3,5‐triazine and 2,4,6‐triazidopyrimidines gives the corresponding septet trinitrenes only as transient species that undergo further photodecomposition to form triplet nitrenes NCN and CNN as well as triplet carbenes NCCCN, HCCN, and HCCCCN.…”
Section: Introductionmentioning
confidence: 99%